A new species of the genus Orthopelma (Hymenoptera: Ichneumonidae: Orthopelmatinae) from China - Zhang, Chuan-Xi (Zootaxa, 2025)
This study describes Orthopelma chinensis sp. nov. (Hymenoptera: Ichneumonidae: Orthopelmatinae), a new species of Orthopelmatinae reported from China, which parasitizes cynipid gall wasps (Cynipidae). The larval stage overwinters within host galls. Phylogenetic relationships between the new species and O. brevicornis Morley and O. mediator (Kusigemati) were inferred using partial mitochondrial cytochrome c oxidase subunit I (COI) gene sequences. A taxonomic key to East Asian Orthopelma species is provided to facilitate identification.